Bladder perivascular epithelioid cell neoplasm: The importance of immunohistochemistry in the diagnosis of an unusual neoplasm. (March 2021) - De Noon, Solange; Ayres, Benjamin; Patel, Uday; Issa, Rami; Ho-Yen, Colan Maxwell
Perivascular epithelioid cell neoplasms represent a group of uncommon mesenchymal tumours with as yet undiscovered benign counterpart. Although perivascular epithelioid cell neoplasms have been described arising in most organ systems as well as in soft tissue and bone, only a small number of perivascular epithelioid cell neoplasms have been reported in the bladder. To date, there is no agreed system for predicting the behaviour of these tumours. We describe a case of a perivascular epithelioid cell neoplasm of the bladder arising in a 57-year-old male and initially diagnosed on biopsy and present a review of the literature focussing on the pathological differential diagnosis and the importance of key histological features in conjunction with a broad immunohistochemical panel. This case report highlights the key features of bladder perivascular epithelioid cell neoplasms that distinguishes these rare neoplasms from other bladder lesions.